Impact of Caudate Lobe Resection on Overall Survival and Liver Disease-Free Survival in Colorectal Liver Metastases: A Pilot Study - Gül, Melih Can; Demirel, Emin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: The objective of this study was to evaluate the impact of the resected caudate lobe on survival, particularly in the context of anatomical resection of liver metastases in colorectal cancers without metastases in the caudate lobe. Materials and Methods: Patient data were extracted from the dataset titled “Preoperative CT and Survival Data for Patients Undergoing Resection of Colorectal Liver Metastases (CRLM).” The analysis specifically concentrated on individuals who underwent complete caudate lobe resection in the absence of radiological signs of metastasis within the caudate lobe itself. To discern the distinct impact of caudate lobe resection on patient outcomes, propensity score matching (PSM) was applied to control for variations across other relevant clinical parameters. Overall survival (OS) and liver disease-free survival (liver DFS) were calculated using the Kaplan–Meier method, while the log-rank test was used to compare survival outcomes between groups. Results: The analysis revealed that patients who underwent total caudate lobe resection exhibited significantly improved OS rates, both in the complete dataset and following PSM (P < .001, HR: 0.43, 95% CI: 0.26-0.72; P = .024, HR: 0.65, 95% CI: 0.59-0.79, respectively). Additionally, liver DFS outcomes were found to be superior in patients who had caudate lobe resection, in both the full dataset and the propensity-matched cohort (P = .014, HR = 0.46, 95% CI: 0.24-0.85; P = .026, HR = 0.5, 95% CI: 0.37-0.79, respectively). Conclusion: These findings suggest that incorporating total caudate lobe resection into the surgical management of CRLM may offer substantial benefits in terms of both OS and liver-specific disease-free survival. Cite this article as:Gul MC, Demirel E. Impact of caudate lobe resection on overall survival and liver disease-free survival in colorectal liver metastases: A pilot study. Turk J Gastroenterol. 2025;36(7):459-466.